Effect of Environmental Moisture on Surface Roughness of FDM and SLA Fabricated Components - Muflikhun, Muhammad Akhsin (JMPM (Jurnal Material dan Proses Manufaktur), 2025)
This study aims to analyze the surface characteristics and moisture contents of three different 3D printed materials, namely Polylactic Acid (PLA) filament, bio-based resin, and standard translucent resin, produced using two distinct manufacturing processes: Fused Deposition Modelling (FDM) for filament materials and Stereolithography (SLA) for resin material. The moisture content was measured using a Moisture Analyzer, and surface characteristics were examined by capturing images through a digital microscope. The results of the moisture content measurement indicated that all three materials exhibited hydrophobic properties with low water content under similar treatments. Among the materials, bio-based resin demonstrated the highest moisture content of 1.53%, followed by translucent resin with 1.26%, and PLA filament with 1.11%. Furthermore, a correlation between applied temperature and moisture content was observed, with translucent resin showing the most stable results, consistently increasing with higher temperatures. In contrast, bio-based resin and PLA filament exhibited unstable behaviours. Surface observation using surface roughness and the digital microscope revealed distinct patterns for the two manufacturing processes. For resin specimens, defects on the surface were evident at lower temperatures and increased with rising temperature. In contrast, PLA filament demonstrated a different surface change pattern, characterized by material melting, leading to a smoother surface. In conclusion, this study sheds light on the surface characteristics and moisture content of 3D printed materials produced through different manufacturing processes. The findings highlight the importance of material selection and processing parameters in achieving desired material properties for various applications in 3D printing.